OP0249 LONG-TERM EXTENSION RESULTS OF RISE-SSC, A RANDOMIZED TRIAL OF RIOCIGUAT IN PATIENTS WITH EARLY DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSSC). (2nd June 2020) - Khanna, D.; Pope, J.; Matucci-Cerinic, M.; Kuwana, M.; Denton, C.; Allanore, Y.; Wosnitza, M.; Truchetet, M. E.; Szücs, G.; Stevens, W.; Steen, V.; Stagnaro, C.; et al.
Abstract : Background: RISE-SSc (NCT02283762 ) was a multicenter Phase IIb trial of riociguat in pts with early (duration ≤18 months) dcSSc and modified Rodnan skin score (mRSS) 10−22 units. Pts were randomized double-blind to placebo or riociguat 0.5–2.5 mg t.i.d. for 52 weeks. The primary endpoint, mRSS change from baseline to Week (Wk) 52, did not reach statistical significance (p=0.08, riociguat vs placebo), but there were favorable trends in some other outcomes. Objectives: To present open-label long-term extension (LTE) results of RISE-SSc. Methods: Pts who completed Wk 52 of double-blind therapy could enter LTE on riociguat. Endpoints included mRSS, adverse events (AEs), and serious AEs (SAEs). Results: Of 60 pts randomized to riociguat and 61 to placebo, 42 (riociguat−riociguat group) and 45 (former placebo group), respectively, entered LTE. At LTE start, mean±SD mRSS was 16.4±3.2 and 16.3±4.2 units, and mean disease duration was 8.9±7.8 and 8.9±5.8 months, in the riociguat−riociguat and former placebo groups, respectively. Other demographics/disease characteristics were also comparable. Median duration of riociguat treatment was 1092 d in riociguat−riociguat pts and 649 d in former placebo pts. Throughout the study, mRSS decreased in both groups (Figure 1 ). From Wk 52 to last visit, mRSS fell by −3.02±5.51 in riociguat−riociguat patients and −3.96±5.43 in former placebo pts. Rates of mRSS regression (decrease by >5 units and ≥25% from Wk 52 to last visit) and of % declines in mRSS were similar in the two groups (Figure 2 ). mRSS progression (increase by >5 units and ≥25% from Wk 52 to last visit) occurred in 1 pt (2%) in each group. During the entire study, rescue therapy agents were used in 15 (36%) riociguat−riociguat pts and 17 (38%) former placebo pts. AEs were reported from Wk 52 to last visit in 82 pts (94%): 40 (95%) riociguat−riociguat and 42 (93%) former placebo. Most common AEs overall: nasopharyngitis (24%), gastroesophageal reflux disease (17%), diarrhea (15%), and hypotension (14%). AEs of special interest (dizziness, postural dizziness, or hypotension) occurred in 5 riociguat−riociguat pts (12%) and 4 former placebo pts (9%). SAEs were reported in 21 (24%) pts: 10 (24%) riociguat−riociguat pts and 11 (24%) former placebo pts, with no SAE reported in >1 patient, no SAEs of special interest, and no deaths. Conclusion: During LTE riociguat treatment, mRSS decreased in both groups from Wk 52 onwards and mRSS progression was uncommon. Riociguat had acceptable safety, similar to the main study, with no new safety signal. Acknowledgments: RISE-SSc was jointly funded by Bayer AG and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure of Interests: Dinesh Khanna Shareholder of: Eicos, Grant/research support from: NIH NIAID, NIH NIAMS, Consultant of: Acceleron, Actelion, Bayer, BMS, Boehringer-Ingelheim, Corbus, Galapagos, Genentech/Roche, GSK, Mitsubishi Tanabi, Sanofi-Aventis/Genzyme, UCB Pharma, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim, Masataka Kuwana Grant/research support from: Acetelion, Consultant of: Acetelion, Bayer, Chugai, Corbus Pharmaceuticals, CSL Behring and Reata Pharmaceuticals. He was a member of the SENSCIS trial Steering Committee (Boehringer Ingelheim), Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer, Yannick Allanore Grant/research support from: BMS, Inventiva, Roche, Sanofi, Consultant of: Actelion, Bayer AG, BMS, BI, Melanie Wosnitza Employee of: Bayer AG, Marie-Elise Truchetet: None declared, Gabriella Szücs: None declared, Wendy Stevens: None declared, Viginia Steen Grant/research support from: The associated affiliation has received grants/research from Boehringer Ingelheim, Corbus Pharmaceuticals, CSL Behring, Eicos, Galapagos, Immune Tolerance Network, Reata, Consultant of: Virginia Steen has acted as a consultant for Boehringer Ingelheim, Corbus, CSL Behring, Eicos, Forbius, Chiara Stagnaro: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Richard Silver: None declared, Elena Schiopu: None declared, Valeria Riccieri: None declared, Frank Kramer Employee of: Bayer AG, Sindhu Johnson Grant/research support from: Boehringer Ingelheim, Corbus Pharmaceuticals, GlaxoSmithKline, Roche, Merck, Bayer, Consultant of: Boehringer Ingelheim, Ikaria, Osamu Ishikawa: None declared, Tomonori Ishii: None declared, Eric Hachlla: None declared, Ellen De Langhe Consultant of: member of advisory board for Boehringer, László Czirják Consultant of: Actelion, BI, Roche-Genentech, Lilly, Medac, Novartis, Pfizer, Bayer AG, Radim Bečvář Consultant of: Actelion, Roche, Tatsuya Atsumi Grant/research support from: Eli Lily Japan K.K., Alexion Pharmaceuticals, Inc., Bristol-Myers Squibb Co., AbbVie Inc., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Astellas Pharma Inc., Consultant of: Gilead Sciences, Inc., Eli Lilly Japan K.K., UCB Japan Co. Ltd., AbbVie Inc., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Speakers bureau: Eli Lilly Japan K.K., UCB Japan Co. Ltd., Bristol-Myers Squibb Co., AbbVie Inc., Eisai Co. Ltd., Otsuka Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Takeda Pharmaceutical Co., Ltd., Astellas Pharma Inc., Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche